Toda lattice realization of integrable hierarchies - Bonora, L.; Constantinidis, C. P.; Vinteler, E. (Kluwer Academic Publ, 1996)
We present a new realization of scalar integrable hierarchies in terms of the Toda lattice hierarchy. In other words, we show on a large number of examples that an integrable hierarchy, defined by a pseudo-differential Lax operator, can be embedded in the Toda lattice hierarchy. Such a realization in terms the Toda lattice hierarchy seems to be as general as the Drinfeld-Sokolov realization.
Keywords: Toda lattice hierarchy; integrable hierarchies; Gelfand-Dickey formalism